Pharmacological Effects of Houttuynia cordata Thunb (H. cordata): A Comprehensive Review - Shahzad Rafiq; Haihong Hao; Muhammad Ijaz; Ahmed Raza (Pharmaceuticals, 2022)
Houttuynia cordata Thunb (H. cordata) is a rhizomatous, herbaceous, and perennial plant widely distributed in Asia. It has multiple chemical constituents, such as alkaloids, essential oils, phenolic acids, and flavonoids used against various health problems. The essential oils and flavonoids are the main components of H. cordata that play an essential role in disease treatment and traditional health care. Moreover, the leaves and stems of H. cordata have a long medicinal history in China. In addition, H. cordata is used against several health issues, such as cold, cough, fever, pneumonia, mumps, and tumors, due to its anti-inflammatory, anti-bacterial, anti-viral, anti-oxidant, and anti-tumor effects. It protects organs due to its anti-inflammatory activity. H. cordata regulates immunity by enhancing immune barriers of the oral cavity, vagina, and gastrointestinal tract, and shows broad-spectrum activity against liver, lung, breast, and colon tumors. However, there are some gaps to be filled to understand its pathways and mechanisms. Mechanisms such as its interaction with cells, cell membranes, and various drugs are important. Studies in relation to the blood–brain barrier, lipophilicity, cAMP signaling, and skin permeability, including pharmaceutical effects, will be very useful. This review includes the biological and pharmacological activities of H. cordata based on up-to-date research.